ANALISIS PERAN PEREMPUAN DALAM PENGELOLAAN SAMPAH RUMAH TANGGA (STUDI PADA MASYARAKAT KOTA BATU) - Uci Yuliati (Jurnal Perempuan dan Anak, 2019)
This research was carried out in Batu City. Women in the house-holds were the respondents of this research. This reseach was very important to be done because women were still dominating the cleaning activities at home in Indonesian society. Therefore it was interesting to learn deeply about their activities, access and control,  beneficial and impact profiles  while they were cleaning house-holds waste.Total area sampling consists three sub-district and respondents were choosen purposively with its criterions who were women as mother in the house-holds. The number of respondents were 73 women. Questionairres were used as an instrument for data collecting. SPSS program was the data analyses for having the  cross-tabulation various  profiles above. The result of analyses shown that women  activities profile could be classify in to their activities from resulting house-hold waste until how they were cleaning their home from waste.Accsess and controll profile shown how they were managing their home waste, how to select it and throw it away to dumpsite then how they comunicated their difficulties to Waste Local Collector.The impact and beneficial profile shown what they had economic impact by selecting, separating and collecting house-holds solid waste. The result of research shows that most of women produced house-holds waste from cooking in their kitchen. Women used to manage household waste from providing boxs or plastic bags, broom, and  then to sweap and to collect it and then through away from home to dumpsite.They used to clean their home from waste everyday dan sometimes their husbands, daugther and son help them. Women who often separate from wet and dry solid house-holds waste could find out the beneficial one namely plastic or glass bottle and paper. After separating it, women  collected and then sold it after a few time for earning money.